Active Sites in a Heterogeneous Organometallic Catalyst for the Polymerization of Ethylene - Culver, Damien B. (ACS Cent Sci, 2021)
[Image: see text] Heterogeneous derivatives of catalysts discovered by Ziegler and Natta are important for the industrial production of polyolefin plastics. However, the interaction between precatalysts, alkylaluminum activators, and oxide supports to form catalytically active materials is poorly understood. This is in contrast to homogeneous or model heterogeneous catalysts that contain resolved molecular structures that relate to activity and selectivity in polymerization reactions. This study describes the reactivity of triisobutylaluminum with high surface area aluminum oxide and a zirconocene precatalyst. Triisobutylaluminum reacts with the zirconocene precatalyst to form hydrides and passivates −OH sites on the alumina surface. The combination of passivated alumina and zirconium hydrides formed in this mixture generates ion pairs that polymerize ethylene.